The Impact of Short-Form Video Marketing, Influencer Relatability, and Trust Signals on Gen Z’s Purchase Intention - Wahyudi, Muhammad Aria; Rahmadhani, May Vitha; Mu'is, Ahmad; Evelyna, Feby (International Journal of Business, Law, and Education, 2025)
This study examines the impact of short-form video marketing, influencer relatability, and trust signals on Generation Z’s purchase intention in Indonesia. Using a quantitative approach, data were collected from 400 respondents aged 18 to 27 who actively engage with short-form video platforms such as TikTok, Instagram Reels, and YouTube Shorts and have made recent online purchases. Multiple linear regression analysis revealed that all three variables significantly and positively influence purchase intention, with influencer relatability showing the strongest effect. The findings underscore the importance of authentic influencer connections, engaging video content, and transparent trust signals in shaping the purchasing decisions of digital-native consumers. This research offers valuable implications for marketers seeking to optimize digital marketing strategies tailored to Generation Z’s unique preferences and behaviors.